Synthese Library
DOI: 10.1007/0-306-48017-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Have Only Men Evolved?

Abstract: HAVE ONLY MEN EVOLVED?*… with the dawn of scientific investigation it might have been hoped that the prejudices resulting from lower conditions of human society would disappear‚ and that in their stead would be set forth not only facts‚ but deductions from facts‚ better suited to the dawn of an intellectual age .…The ability‚ however‚ to collect facts‚ and the power to generalize and draw conclusions from them‚ avail little‚ when brought into direct opposition to deeply rooted prejudices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…If women seek more connection and attend more to others, it is because they hold lower status within society. This strain of literature has roots in the feminist social construction of reality literature focusing on how collective knowledge bases are constructed and maintained (e.g., Flax, 1983;Harding, 1983;Hartman & Messer-Davidow, 1991;Hubbard, 1983). These authors revealed ways that even scientific knowledge is shaped by the beliefs, values, and ideals of those who have the power to define what is "real" and what is "true."…”
Section: Focusing On Power Differencesmentioning
confidence: 99%
“…If women seek more connection and attend more to others, it is because they hold lower status within society. This strain of literature has roots in the feminist social construction of reality literature focusing on how collective knowledge bases are constructed and maintained (e.g., Flax, 1983;Harding, 1983;Hartman & Messer-Davidow, 1991;Hubbard, 1983). These authors revealed ways that even scientific knowledge is shaped by the beliefs, values, and ideals of those who have the power to define what is "real" and what is "true."…”
Section: Focusing On Power Differencesmentioning
confidence: 99%
“…The critique of androcentric bias dates back to Darwin's (1871) account of sexual selection (Brown Blackwell, 1875;Gamble, 1894;reviewed in Hamlin, 2014). In the 1970s and 1980s, as part of their resistance to sociobiology's apparent inscription of oppression in biology, biologists, humanists, and social scientists challenged theories, assumptions, and methodologies related to sexual selection theory, particularly its application to humans (e.g., Bleier, 1984;Hubbard, 1979. Biologists critiqued practices that deemphasized the study of female behaviors or that resulted in stereotypical representations of female and male relationships.…”
Section: Critique Of Sexual Selection Theorymentioning
confidence: 99%
“…Over the past 2 decades, however, feminist theorists have demonstrated that many theories are permeated specifically by androcentric biases missed entirely by earlier investigators. These feminist theorists have been especially concerned with identifying the androcentric biases that pervade arguments that purport to demonstrate a biological basis for malelfemale differences in cognitive ability or personality (see, for example, Fausto-Sterling 1992; Hubbard 1983).…”
mentioning
confidence: 99%